Struktur dan Keunikan Bumi: Berkenalan dengan Planet Kita Melalui Kearifan Lokal Yang Menghormati Alam - Alisia Zahro’Atul Baroroh; Umi Mahmudah (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
This study aims to explore the structure and uniqueness of Earth through the lens of local wisdom that respects nature, and to investigate how traditional knowledge can offer valuable insights into our planet and the relationship between humans and the environment. A qualitative approach was employed, involving a literature review and analysis of traditional texts, myths, folktales, and cultural practices related to the understanding of the universe, Earth's structure, and human interaction with ecosystems. The findings reveal that many indigenous cultures around the world view Earth as a living entity, with an interconnected relationship between humans and the surrounding environment. This understanding is reflected in various rituals, agricultural systems, and environmental policies that emphasize balance and sustainability. Furthermore, local wisdom often stresses the importance of respecting nature as an integral part of harmonious living on Earth. The implications of this research highlight the importance of integrating local wisdom into environmental education, sustainable development policies, and natural resource management to foster a more harmonious and sustainable relationship between humans and the Earth.